Global quantitative and qualitative assessment of drought research from 1861 to 2019. (15th February 2022) - Ekundayo, Olapeju Yewande; Abiodun, Babatunde J.; Kalumba, Ahmed M.
Abstract: Over the last 150 years, there has been a dramatic increase in research focusing on droughts in every part of the world, due to their negative impacts on multiple sectors, the functioning of ecosystems and human wellbeing. However, our understanding of the long-term trends of drought-related research remains limited. Therefore, this study is aimed at providing a generalised quantitative and qualitative synthesis of drought-related research publications from 1861 to 2019 in the Scopus database, using bibliometric and science mapping analytics. Title-speciﬁc field drought-related articles were mined and analysed for explanatory characteristics to identify different research trends, global and national interests and their contributions'. The results of the synthesis revealed a total of 26, 221 articles from 45, 329 authors and 3181 journals. The annual research production in drought-related research thus exhibited a 7.87% annual growth rate during this period from 1861 to 2019. Drought as a central theme witnessed a mean growth rate (MGR) of 8170% in the last 3 years (2017–2019). The prevailing topics include drought tolerance, resilience, climate change, and drought resistance, which had MGRs of 1100%, 530%, 2030% and 70% in 2017–2019, respectively. With an MGR of 1030%, remote sensing appeared to be a widespread method used in the monitoring of meteorological drought (600%), agricultural drought (730%), and hydrological drought (330%). Four trending thematic areas identified in drought-related research from 1861 to 2019 were climate change-related; physiology and biochemistry in plant/herb photosynthesis; molecular genetics and mechanisms of drought impacts (stress), tolerance and resistance in crops/plants; and emerging concept related to the circadian rhythms of biological systems in drought conditions. It also emerged from an analysis of the thematic areas that drought-related research in South Africa focused on agriculture and food-security, water-security, environmental sustainability, socioeconomics (among others) during the relevant period.